Directing memory content to attentional templates: The finiteness effect of predictive information - Chen, Zhen; Li, Qiankai; Li, Xinyu (Frontiers in Psychology, 2023)
Visual search can be accelerated according to the properties of information stored in memory and prior knowledge of the upcoming work. This helps the searcher direct their attention to (or avoid) items that match these properties. Meanwhile, the different functional areas where these properties exist become attentional templates. Compared with neutral conditions, the use of attentional templates significantly benefits reaction time (RT). However, previous studies may have confounded the memory-driven and cue-driven effects. Thus, it is less clear which factor influences the template benefits. Modeled on previous research, this study employed a new design to explore the independent effects of textual cues, thus finding an inverse effect; that is, positively cueing an item retained in memory did not improve behavioral performance, but negatively cueing an item did achieve such an enhancement. Moreover, positive cueing even resulted in some damage to attentional searching under some conditions, thus indicating that the advantages of positive cueing reported in previous studies may actually be driven by working memory, while the effects of negative cueing are driven by prior knowledge.